Uji Aktivitas Antibakteri Ekstrak, Fraksi Air, Fraksi Etil Asetat, Fraksi n-Heksan Daun Petai Cina (Leucaena leucocephala) Terhadap Bakteri Staphylococcus aureus ATCC 25923 - Muhammad Andira Ibnu Shina; Tatiana Siska Wardani; Kusumaningtyas Siwi Artini (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Shina, mai., 2024, test of antibacterial activity of extract, water fraction, ethyl acetate fraction, and n-hexane fraction of chinese petai leaf (leuncaena leucocephala) against staphylococcus aureus atcc 25923, thesis, faculty of health sciences, duta bangsa university, surakarta one of the traditional medicines that currently has the potential to be developed is the chinese petai plant (leucaena leucocephala). Chinese petai leaves are used by the people of indonesia as a remedy for new and swollen wounds. Staphylococcus aureus is a gram-positive coccus bacterium that is the main pathogen in humans. Almost everyone has experienced a wide variety of staphylococcus aureus infections during their lifetime, from severe food poisoning to minor skin infections. The methods used in this study are diffusion and dilution. The purpose of this study was to determine the antibacterial activity of water extracts and fractions, ethyl acetate fractions, and n-hexane fractions of chinese petai leaves (leuncaena leucocephala), to find the most active extracts and fractions based on their inhibitory zones, and to determine the khm and kbm of the most active extracts against staphylococcus aureus atcc 25923. Based on research conducted on ethanol extract, water fraction, ethyl acetate fraction, and n-hexane fraction of chinese petai leaves have antibacterial activity against staphylococcus aureus atcc 25923. The most active extract in inhibiting staphylococcus aures atcc 25923 judging from its inhibition zone value is ethanol extract. Ethanol extract of chinese petai leaves has the same khm and kbm values, namely at a concentration of 25%.